An extended approach to appraise electricity distribution and carbon footprint of bitcoin in a smart city - Sharma, Ayushi; Sharma, Pratham; Bamotra, Harsh; Gaur, Vibha (Frontiers in Big Data, 2023)
Modern nations are buzzing about "Smart Cities", which have a fast-paced and sustainable infrastructure. Smart cities are envisioned to have green computing capabilities and immunity against cybercrimes. Bitcoin and other cryptocurrencies of its kind have transformed the way organizations and Governments perceive smart currency. Due to its inherent decentralization and immutability, blockchain technology with encryption is ideally suited to urban environments. Bitcoin has the potential to magnify and expand its functionalities in smart transactions involving funds transfer. But, the repercussions of a blockchain from an energy distribution standpoint can’t be overlooked despite having a significant effect on society and the economy. Crypto mining despite being a highly effective transaction system consumes a huge chunk of energy that usually comes from high Carbon emissive sources of power. Patch Methodology uses an energy-centric system to evaluate the Energy consumption of Bitcoin using parameters such as network hash rate and efficiency of hardware. However, this methodology stops at energy consumption and shows inconsistency with accuracy when extended to compute Carbon emissions. To manage emissions, it is mandatory to have an accurate and robust measurement mechanism in place. This paper proposes an extended Patch methodology that expands the current approach of power Consumption to compute the bounds of electricity consumption and Carbon emissions of Bitcoin Mining. Due to the plethora of uncertain and unknown parameters involved, it is challenging to compute a single value of electricity consumption and Carbon Footprint with precision. The electricity consumption of Bitcoin using the proposed approach was estimated between 38.495 to 120.728 TeraWatt Hours for the year 2021 while the Carbon emissions ranged between 2.12 to 45.379 Million Metric Tons. Miners and mining pools may incorporate green solutions and opt for environment-friendly energy sources for mining hardware.